2004
DOI: 10.1007/s00125-004-1617-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiac autonomic neuropathy in type 1 diabetes mellitus

Abstract: Aims/hypothesis: Cardiac autonomic neuropathy (CAN) is associated with increased morbidity and mortality in type 1 diabetes. Apart from glycaemic control, risk factors for CAN have not been extensively studied. Methods: As part of the EURODIAB Prospective Complications Study, CAN-defined as either a loss of heart rate variability or postural hypotension on standing-was assessed at baseline and follow-up (7.3±0.6 years from baseline) in patients with type 1 diabetes. Results: Follow-up measurements were availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
4
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 38 publications
10
122
4
15
Order By: Relevance
“…This confirms that diabetic neuropathy is indeed prevalent among patients in the early stages of type 2 diabetes. Several risk factors for the development of neuropathy exist [1,18,[21][22][23]. However, trial evidence of treatment to prevent the development of CAN in people with type 2 diabetes is sparse [1,12,24].…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that diabetic neuropathy is indeed prevalent among patients in the early stages of type 2 diabetes. Several risk factors for the development of neuropathy exist [1,18,[21][22][23]. However, trial evidence of treatment to prevent the development of CAN in people with type 2 diabetes is sparse [1,12,24].…”
Section: Discussionmentioning
confidence: 99%
“…There may also be links between PP and CAN [24], between aortic stiffness and CAN [13,14], and between arterial stiffness, cardiovagal baroreflex sensitivity and postural BP changes [35]. Increased SBP was identified as a factor associated with an increased risk of developing CAN in the cohort of T1DM patients in the EURODIAB Prospective Complications Study [16]. Also, we previously reported a significant inverse relationship between pulsatile stress and baroreflex gain as a marker of CAN in middle-aged patients with T1DM [26].…”
Section: Discussionmentioning
confidence: 99%
“…Both CAN [10] and increased PP [11,12] are considered to be independent risk factors of cardiovascular disease and total mortality in T1DM patients. Furthermore, CAN may be linked to aortic stiffness [13,14], endothelial dysfunction [15] and increased SBP [16] or PP [17] in T1DMpatients. Moreover, CAN is known to be associated with a greater risk of orthostatic hypotension [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This may be responsible for certain disabling symptoms, painless myocardial infarction, and sudden deaths 4,5,[14][15][16][17] . In our study, 43% of the patients showed the involvement of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%